Gestión de las cuentas por cobrar y su impacto en la liquidez de la distribuidora Walter Caicedo S.C.C., periodo 2017-2018. - Vera Veliz, Eva Lucía (2020)
The present investigation describes the shortcomings found in the processes related to the provision of credit services of the Hotel Punta del Mar. The objective of the study was to evaluate the management of Accounts Receivable based on the accounting and financial procedures applied by management for the Measurement of the liquidity of the company and thereby establish alternative solutions that strengthen operations. The methodology used was of a descriptive type with an idea to defend, emphasizing the inductive method, analysis and synthesis, in addition a bibliographic study of specialized texts inherent to the subject treated and field visits were conducted where interviews were applied to collaborators in the financial area, as well as an observation sheet in the treatment of economic information. The results show that the company does not have regulations that contain policies and procedures for credits and collections, a situation that represents a weakness in the internal control systems because the activities that each area should develop when evaluating, approving, supervising credits and managing are unknown. collections, affecting their liquidity. Keywords: Management, accounts receivable, liquidity, credit, collection.